The cognitive interview for suspects: A test with customs officers. Issue 3 (2nd March 2022) - Noc, Mathilde; Ginet, Magali; Deslauriers‐Varin, Nadine
Abstract: The current study aimed at testing the impact of the cognitive interview for suspects (CIS) used by trained custom officers on the quantity of gathered details, compared to a control standard interview (SI) used by untrained officers. Forty‐five mock‐suspects were required to perform a series of actions and each was interviewed by a pair of customs officers. Participants had to give statements containing truthful parts and deceptive parts. The CIS elicited significantly more details than the SI. Truthful parts of the statements contained more details than deceptive parts. An interaction effect revealed that the CIS elicited a higher number of action details in truthful parts. It is worthwhile for professionals in the field to adopt the CIS, which provides valuable benefits for information gathering. Moreover, the increase in action details raise the question of considering it as a possible lie detection tool.